2021
DOI: 10.3390/foods10081849
|View full text |Cite
|
Sign up to set email alerts
|

The Bioaccessibility of Phenolics, Flavonoids, Carotenoids, and Capsaicinoid Compounds: A Comparative Study of Cooked Potato Cultivars Mixed with Roasted Pepper Varieties

Abstract: An in vitro method was used to assess the bioaccessibility of phenolics, flavonoids, carotenoids, and capsaicinoid compounds in different cooked potatoes mixed with roasted peppers (Capsicum annuum), Joe Parker (JP, hot), and Sweet Delilah (SD, sweet). The present study identified differences in the bioaccessibility of bioactive compounds among the potato cultivars (Solanum tuberosum) Purple Majesty (PM; purple flesh), Yukon Gold (YG; yellow flesh), Rio Grande Russet (RG; white flesh) and a numbered selection … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…The quantification of individual phenolics was carried out as described by Albishi et al. [1 7 ] A reverse phase column (250 × 4.6 mm, 5 µm Purospher RP‐18e, Merck, Germany) was used on the LaChrom HPLC system (Merck‐Hitachi Darmstadt, Germany). The injection volume was 20 µL (injected in rheodyne injector) and the wavelength used was 324 nm.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantification of individual phenolics was carried out as described by Albishi et al. [1 7 ] A reverse phase column (250 × 4.6 mm, 5 µm Purospher RP‐18e, Merck, Germany) was used on the LaChrom HPLC system (Merck‐Hitachi Darmstadt, Germany). The injection volume was 20 µL (injected in rheodyne injector) and the wavelength used was 324 nm.…”
Section: Methodsmentioning
confidence: 99%
“…Cooking of potatoes mixed with peppers is reported to enhance the bioaccessibility of polyphenolics. [7] The cooking methods also result in physical, chemical, and enzymatic modification of phytochemicals leading to sensory, and textural changes in food. [8,9] However, cooking may also cause the loss of some of phytonutrients and the formation of undesired products.…”
Section: Introductionmentioning
confidence: 99%
“…6 One major factor that affects bioaccessibility is food processing which can increase some phytonutrients and decrease others. 6 Till date, bioaccessibility of acrylamide, 7 phenolics, flavonoids, carotenoids, 8 vitamin C, 9 lutein, and zeaxanthin 10 has been studied in potatoes.…”
Section: Introductionmentioning
confidence: 99%
“…Hamed et al (2021) reported mixing roasted peppers, namely, cultivars Joe Parker and Sweet Delilah with the potato cultivar Yukon Gold (yellow flesh) to significantly enhance the bioaccessibility of polyphenols and carotenoids. 8 As reviewed by Thakur et al, the change in pH in gut environment affects the bioaccessibility of phytonutrinets. Researchers have reported decrease in concentration of bioaccessible phytonutrients such as total polyphenols, flavonoids, and anthocyanins when shifted from acidic gastric phase to alkaline intestinal phase.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation